“Aku Cinta Diriku secara Rasional dan Spiritual”: Tinjauan Pustaka Sistematis tentang Self-Love dalam Perspektif Islam dan Barat - Hani Fadilah Humaira; Fuad Nashori (Universitas Islam Negeri Imam Bonjol Padang, 2026)
Abstract: This study aims to determine the similarities and differences of self-love in the perspective of Islamic psychology and Western psychology as well as its synthesis and application in a modern context. The method used is PRISMA (Preferred Reporting Items for Systematic Reviews and Analyzes). The sources of literature used are Scopus, Mendeley, and Garuda. The limitations of the reviewed journals are research using Indonesian and English, spanning the years 2020-2025, and research in the form of articles with the keywords